Protein kinase D1 deletion in adipocytes enhances energy dissipation and protects against adiposity. (5th November 2018) - Löffler, Mona C; Mayer, Alexander E; Trujillo Viera, Jonathan; Loza Valdes, Angel; El‐Merahbi, Rabih; Ade, Carsten P; Karwen, Till; Schmitz, Werner; Slotta, Anja; Erk, Manuela; Janaki‐Raman, Sudha; Matesanz, Nuria; et al.
Abstract: Nutrient overload in combination with decreased energy dissipation promotes obesity and diabetes. Obesity results in a hormonal imbalance, which among others activates G protein‐coupled receptors utilizing diacylglycerol (DAG) as secondary messenger. Protein kinase D1 (PKD1) is a DAG effector, which integrates multiple nutritional and hormonal inputs, but its physiological role in adipocytes is unknown. Here, we show that PKD1 promotes lipogenesis and suppresses mitochondrial fragmentation, biogenesis, respiration, and energy dissipation in an AMP‐activated protein kinase (AMPK)‐dependent manner. Moreover, mice lacking PKD1 in adipocytes are resistant to diet‐induced obesity due to elevated energy expenditure. Beiging of adipocytes promotes energy expenditure and counteracts obesity. Consistently, deletion of PKD1 promotes expression of the β3‐adrenergic receptor (ADRB3) in a CCAAT/enhancer binding protein (C/EBP)‐α‐ and δ‐dependent manner, which leads to the elevated expression of beige markers in adipocytes and subcutaneous adipose tissue. Finally, deletion of PKD1 in adipocytes improves insulin sensitivity and ameliorates liver steatosis. Thus, depletion of PKD1 in adipocytes increases energy dissipation by several complementary mechanisms and might represent an attractive strategy to treat obesity and its related complications. Synopsis: Nutrient overload results in hormone imbalance and activation of DAG‐dependent signaling cascades including protein kinase D1 (PKD1). Here, mouse models reveal a causal role for PKD1 in controlling mitochondrial metabolism and lipid accumulation in fat cells, promoting obesity and diabetes. PKD1 drives lipogenesis by inhibiting AMPK. PKD1 inhibits mitochondrial fragmentation and respiration in adipocytes. PKD1 suppresses C/EBP‐α/δ‐dependent transcription of β3 adrenergic receptor and beige adipocyte markers. Deletion of PKD1 in adipocytes protects mice from obesity, type 2 diabetes and liver steatosis in vivo . Abstract : Protein kinase D1 exerts physiological roles in fat tissue and functions to stimulate lipogenesis and triglyceride accumulation upon nutrient overload, regulating whole‐body energy homeostasis.